2012
DOI: 10.1111/j.1600-9657.2011.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination injuries 2. The risk of pulp necrosis in permanent teeth with subluxation injuries and concomitant crown fractures

Abstract: A concomitant crown fracture and no response to EPT at the initial examination may be used to identify teeth at increased risk of PN following subluxation injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 21 publications
4
71
2
1
Order By: Relevance
“…Current literature suggests that up to 9 days delay between the time of trauma and treatment may have minimal effect on the outcome of Cvek pulpotomies . The outcome does not appear to be affected by the exposure size as long it is less than 4 mm . A Cvek pulpotomy will have a better prognosis in a tooth with an open apex than in a tooth with a closed apex . This is even more relevant in cases with a concomitant luxation injury .…”
Section: Discussionmentioning
confidence: 97%
“…Current literature suggests that up to 9 days delay between the time of trauma and treatment may have minimal effect on the outcome of Cvek pulpotomies . The outcome does not appear to be affected by the exposure size as long it is less than 4 mm . A Cvek pulpotomy will have a better prognosis in a tooth with an open apex than in a tooth with a closed apex . This is even more relevant in cases with a concomitant luxation injury .…”
Section: Discussionmentioning
confidence: 97%
“…By using multivariate regression statistics, Lauridsen et al (32)(33)(34)(35) found in combined luxation-crown fracture injuries that beside the already known variables for predicting PN after luxation injuries (ie, luxation diagnosis and stage of root development), reaction to electrical pulp testing (EPT) at the time of injury played an important role. Thus, teeth that did not respond to EPT had a significantly greater risk of developing PN in the first year after injury.…”
Section: Crown Fractures: Predicting Pulpal Responsementioning
confidence: 98%
“…The prevalence of trauma in the permanent dentition has been reported to range from 2.6% to 35% with a greater incidence occurring between the ages of 7 and 15 , when most permanent teeth are in an incomplete root development stage. Unfortunately, approximately 50% of the traumatized teeth may be diagnosed with pulpal necrosis , with a greater incidence occurring following severe injuries such as intrusions and avulsions and combination injuries . Thus, children with a developing dentition are at an increased risk for sustaining injury that could lead to pulpal necrosis.…”
Section: Common Features Of Current Repsmentioning
confidence: 99%